2010
DOI: 10.1590/s0100-40422010000900033
|View full text |Cite
|
Sign up to set email alerts
|

The history of the rectilinear diameter law

Abstract: Recebido em 5/1/10; aceito em 29/4/10; publicado na web em 1/9/10The formulation of the so-called law of rectilinear diameter for the determination of the critical volume of substances in the concluding decades of the nineteenth century became in a very useful and acceptably exact alternative tool for researchers in the field of critical phenomena. Its corresponding original expression, and even those of its early few modifications, were so mathematically simple that their use did not limit to exclusively cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 23 publications
0
56
0
Order By: Relevance
“…For simple liquids, whence the linear law is an accurate representation, the limiting density on the metastable coexistence line is 2y m , where y m is the density constant in the LRDs. LRD has a long history [78] in the determination of van der Waals hypothetical 'critical density', which the recent work we have discussed argues does not exist as such [79,80]. The significance of the limiting density constant, however, in its relation to an amorphous ground state with a thermodynamic status, has, until recently, been overlooked [85].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For simple liquids, whence the linear law is an accurate representation, the limiting density on the metastable coexistence line is 2y m , where y m is the density constant in the LRDs. LRD has a long history [78] in the determination of van der Waals hypothetical 'critical density', which the recent work we have discussed argues does not exist as such [79,80]. The significance of the limiting density constant, however, in its relation to an amorphous ground state with a thermodynamic status, has, until recently, been overlooked [85].…”
Section: Discussionmentioning
confidence: 99%
“…They found that square-well liquids in the coexistence range of temperatures obey the law of rectilinear diameters (LRDs) 5 [78]. They fitted the density curves of the coexisting phases to the following equations which imply obedience to LRD:…”
Section: Liquid-vapour Coexistencementioning
confidence: 99%
“…This semi-empirical method consists in plotting the midpoints of each tie-line, defining the associated straight line with the better regression parameters, and then extrapolating this latter until its intersection with the experimental binodal curve [3]. However, this graphical method needs a fairly good symmetry between both sides of the binodal curve, which provides a good linearity of the midpoints.…”
Section: Straight Diameter Methodsmentioning
confidence: 99%
“…In 150 years since Andrews' discovery of a critical temperature (T c ), however, nobody has reported a direct measurement of a liquid-gas "critical volume" [3]. Moreover, empirically parameterized cubic equations-of-state, in the spirit of van der Waals, have required ever-increasing numbers of adjustable parameters to reproduce the thermodynamic state functions with 5-6 figure numerical accuracy along critical and supercritical isotherms [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, empirically parameterized cubic equations-of-state, in the spirit of van der Waals, have required ever-increasing numbers of adjustable parameters to reproduce the thermodynamic state functions with 5-6 figure numerical accuracy along critical and supercritical isotherms [3,4]. This progressive inadequacy of cubic equations-of-state is indicative that the hypothesis of supercritical "continuity of gas and liquid" may be suspect.…”
Section: Introductionmentioning
confidence: 99%